Pengaruh Budaya Organisasi Dan Kompensasi Terhadap Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan (Studi Kasus Pada Generasi Baby Boomers, X, Y Dan Z) - Stevanny Novianti Saliman (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to analyze the influence of organizational culture and compensation towards job satisfaction in improving the performance of employees on the baby boomers, generation x, y, and z. Respondents in this research is done by taking a employee population from some random generation of working around the area of West Jakarta and Tangerang. The method is carried out in the form of survey method with the dissemination of questionnaires with population numbers 150 people. The results of this research show that the culture of the Organization and compensation have levels of influence significantly to job satisfaction in improving employee performance. Adjustment of organizational culture in the work environment and the granting of compensation in accordance with the work that is given to the employee can be influential with the job satisfaction of employees in a company as well as improve productivity or performance employees at the company